Dry matter yield, earliness and plant regeneration of different subclover cultivars in southern Italy - Corleto A.; Cazzato E. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Research was conducted over a 4-year period (1994-1997) on the Gaudiano di Lavello field (Basilicata region), 180 m a.s.l., 41° 3' N, 15° 48' E, on a sandy-loam soil. Twelve cultivars of Trifolium brachycalycinum (3), Trifolium subterraneum (7) and Trifolium yanninicum (2) were compared using a randomized block design with 3 reps and a plot area of 1 m2. The following parameters were analysed for the 4-year period: (i) dry matter yield (DMY); (ii) biomass distribution during the year (BD); (iii) plant height (PH); (iv) flowering earliness (FE); and (v) plant regeneration (PR). DMY as a mean of a 4-year period ranged from 6.8 (T. brachycalycinum cv. Nuba) to 4.1 t/ha (T. subterraneum cv. Junee). BD calculated in fall, winter and spring period reached the highest values in spring (56%) while it was lower in winter (28%) and fall (16%). pH shows a wide range of variability between cultivars. As to FE it ranged from April 3 (T. subterraneum cv. Woogenellup) to April 23 (T. yanninicum cv. Larisa). PR, expressed as number of seedlings/m2, varied from 2808 (T. subterraneum cv. Enfield) to 1555 (T. brachycalycinum cv. Nuba).
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)